Effectiveness of intervention package on behaviour modification of children with attention deficit hyperactivity disorder among their parents and teachers - E.SRIGNANASOUNDARI,; Dr.S.VIJAYALAKSHMI,; Dr.R. VIJAYARAGHAVAN Ph.D, (International Journal of Pharma and Bio Sciences, 2017)
Attention Deficit Hyperactivity Disorder (ADHD) is one of the most common psychiatric disorders characterized by inappropriate levels of inattention, hyperactivity and impulsivity. The world wide prevalence of ADHD varies 4% to 8% in U.S, 7.6 to 9.5% in Korea, 10 to 20% in India. The worldwide prevalence of ADHD is 5.2% in 3-4 years and 29.2% in 11-12 years. Aim of the study to assess the behavior of ADHD children before and after the intervention as rated by their parents and teachers and to associate the behaviour of ADHD children with their selected demographic variables. Time series research design was used. The study was conducted at Adhiparasakthi Annai Illam, special school of Melmaruvathur in Kancheepuram district by using total enumerative sampling technique. Conner’s parents rating scale and Conner’s teacher rating scale was used to assess the behavior of ADHD children among their parents and teachers. Total of 10 ADHD children were selected. In parents rating scale before and after intervention package 50% of children had mild behaviour symptoms, 30% had moderate behaviour symptoms and 20% had severe behaviour symptoms. After the intervention package 70% of children had mild behaviour symptoms, 20% had moderate behaviour symptoms and 10% had severe behaviour symptoms in post test. In teachers rating scale before intervention package 100% of children had severe behaviour symptoms. After the intervention package 40% of children had mild behaviour symptoms, 50% had moderate behaviour symptoms and 10% had severe behaviour symptoms. Over all findings of the study reported that the intervention packages had been effective and brought good changes in the behavior of ADHD children.